Sentinel Lymph Node Biopsy in Early Breast Cancer Using the Indocyanine Green Fluorescence Technique: A Validation Study - Khang, Loh Soon; Baharudin, Suraya; Abdul Latiff, Juliana; Mahamad Dom, Siti Aishah; Suhaimi, Shahrun Niza (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Introduction: Sentinel lymph node biopsy (SLNB) is now recognized as the standard of care for early breast cancer patients with negative axillary lymph nodes. Various approaches for Sentinel Lymph Node (SLN) identification using either the blue dye method or scintigraphy alone or their combination have been proposed. However, this method is costly and may not be applicable in certain developing countries. SLNB involving the use of indocyanine green (ICG) offers several advantages, and it is valid and safe when in direct comparison with the blue dye method and scintigraphy. Hence, we performed SLNB using this method in early breast cancer as the first center that involves the use of ICG in Malaysia. We performed validation study on this method with the aims to determine its sensitivity and safety profile. MATERIALS AND METHODS: This is a validation and non-randomised prospective observational study involving 20 patients underwent SLNB wherein ICG is used for localisation. The patients were recruited according to the recommendations stipulated in the Malaysia Clinical Practice Guideline. RESULT: The average number of SLNs removed per patient was 4.0 (range, 3–6) with sentinel lymph nodes detection rate at 98.75% (79/80). The false negative rate is at 5%. No adverse events were observed in all cases. CONCLUSION: The ICG fluorescence method is simple, reliable and safe. Moreover, it demonstrates a high SLN detection rate with a low false-negative rate, and it does not require a special instrument for radioisotope use.